Pengaruh Aktiva dan Kualitas Agen terhadap Kemampulabaan, Pertumbuhan Laba, dan Nilai Perusahaan : Studi Kasus pada ISAT dan GGRM - Achmad, Noor (Jurnal Ilmiah Ranggagading (JIR), 2006)
Some key issues in business are Total Assets (TA), Quality of Agent (AQ), Profitability (P), and Sustainable Growth (G). Those variables are interrelated to each other in creating the firmâs value. Setting up those variables in such proportional level and keeping them stable to achieve maximum firmâs value is a crucial duty of the Agent. In real world this duty is not so easy, since there are a lot of other variables which coming from internally and the outside of the firm. The fact that it should be such cooperation between them. The outcomes of the study to ISAT and GGRM in the period 1995-2004 are that, in this case, TA and AQ are not always has significant correlation. TA Agent and the Owner in determining certain crucial decisions (for example, dividend policy decision) that strive to keep maintaining the investorâs trust to the company. This way could lead the firmâs stock price to be stable or gradually increase from time to time has no significant influence to P and G. Even TA has insignificant influence to V. Meanwhile AQ has significant influence in creating P. Simultaneously TA and AQ has a high significant correlation and influence in creating P, but not always significant in creating G and V. The case is understandable since G is an impact of dividend policy that stipulated by the owner or shareholders. While V reflecting market appreciation based on many factors, one of those is G. Keywords: Agent Quality, Dividend Policy, Profitability